2021
DOI: 10.1109/ojits.2021.3057481
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructural, Decisional and Organizational Aspects to Use Mode Shift to Handle Disruptions in Freight Transport: Literature and Expert Survey

Abstract: Freight transport disruptions in recent years caused production shutdowns in the industry, supply shortages and high economic damage around the world. In practice, contingency strategies from transport operators are often weak and disruption management fails to handle the situation sufficiently. Despite availability of data collection, academic optimization approaches, and multiple initiatives for coordinated multimodal management in case of disruptions, there are multiple infrastructural, decisional and organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…To improve handling them, several systems are under development (e.g. real-time information, disruption management, see for instance [66], [67]). However, in Switzerland, there are no guidelines for estimating or understanding the actual societal costs for the non-availability of transport systems, whether unplanned or planned (e.g., maintenance).…”
Section: Improvements In Supply Characteristicsmentioning
confidence: 99%
“…To improve handling them, several systems are under development (e.g. real-time information, disruption management, see for instance [66], [67]). However, in Switzerland, there are no guidelines for estimating or understanding the actual societal costs for the non-availability of transport systems, whether unplanned or planned (e.g., maintenance).…”
Section: Improvements In Supply Characteristicsmentioning
confidence: 99%
“…In the field of multimodal management during a disruption in freight transport, previous studies showed that mode shift as a response to disruption (assuming multiple modes are available) can reduce both the delay and cost ( 4 ). From a network perspective, transport systems of different modes can, especially during disruptions, complement each other and provide alternatives for freight transportation if infrastructure and service access are available ( 5 ).…”
mentioning
confidence: 99%